Mixed messages: The ambiguity of the MOD chip and pirate cultural production for the Nintendo DS. (August 2014) - O'Donnell, Casey
This essay 1 examines the ambiguous character of videogame console modification chips (MOD chips) in the space of videogame piracy. While it is possible for these chips to be used to "pirate" versions of games for these devices, they also expand the utility of the devices by adding capabilities. Perhaps more significantly, MOD chips also enable users to create software and videogames that run on these consoles outside the typical rules and regulations of the videogame industry. Ethnographic work amongst Nintendo DS ("dual screen") MOD communities is examined to illuminate this understudied space of cultural production.